Challenges Encountered by Women and Girls with Disabilities in Iligan City and Lanao del Norte during Covid-19 Pandemic - B. GAVIOLA, JR., FELIX; C. SILOR, ADELFA; P. TRINIDAD, GENARA; GAVIOLA, LINDY LOU (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The most vulnerable groups include women, children, and those with disabilities. They had to deal with differences in income. Women and girls with disabilities must be evaluated in this research study to establish if they have suffered financial disparity and gender inequality, notably during pandemic times, which is goal #5 of the United Nations Sustainable Development Goals (SDGs). This study aimed to determine the challenges women and girls with disabilities encountered in Iligan City and Lanao del Norte during the covid-19 pandemic. Women and girls with disabilities have been overlooked by feminist and disability rights activists, putting them at a disadvantage. W&GWDs are more likely to encounter “double discrimination,” which includes violence, abuse, and marginalization based on gender. A mixed method was used, a combination of quantitative and qualitative. In quantitative, the survey questionnaire used the five-point Likert Scale. Purposive sampling was used in choosing the 127 respondents. Findings suggest that women and girls with disabilities are frequently overlooked at the national and sectoral levels, as well as in overall policy directions, due to ineffective related laws and regulations, sociocultural impediments, and a lack of public awareness, which should be part of the plans during the covid-19 pandemic. In an atmosphere of the ongoing pandemic, women survivors of covid-19 are known to have significantly more significant problems in accessing care. In conclusion, the government should launch an advocacy program to empower women and girls with disabilities during times of crisis.